2015
DOI: 10.1016/j.antiviral.2015.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel anti-hepatitis C virus agents by a quantitative high throughput screen in a cell-based infection assay

Abstract: Hepatitis C virus (HCV) poses a major health threat to the world. The recent development of direct-acting antivirals (DAAs) against HCV has markedly improved the response rate of HCV and reduced the side effects in comparison to the interferon-based therapy. Despite this therapeutic advance, there is still a need to develop new inhibitors that target different stages of the HCV life cycle because of various limitations of the current regimens. In this study, we performed a quantitative high-throughput screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…Therapeutic regimens are not chosen solely based on patient needs but are determined by what resources are available from the point of view of the health care provider. Advancements in HCV cell culture systems allowed us to approach this problem from a phenotypic perspective, to develop treatments that have a different mode of action from the existing DAAs, and are thus likely synergistic with currently available drugs due to their mechanism of action [21][22][23]. We have previously shown that CCZ inhibits the entry step of HCV infection and exhibits synergistic activity with currently approved anti-HCV agents in vitro [14,24].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic regimens are not chosen solely based on patient needs but are determined by what resources are available from the point of view of the health care provider. Advancements in HCV cell culture systems allowed us to approach this problem from a phenotypic perspective, to develop treatments that have a different mode of action from the existing DAAs, and are thus likely synergistic with currently available drugs due to their mechanism of action [21][22][23]. We have previously shown that CCZ inhibits the entry step of HCV infection and exhibits synergistic activity with currently approved anti-HCV agents in vitro [14,24].…”
Section: Discussionmentioning
confidence: 99%
“…Several compounds targeting other GPCRs were identified as HCV inhibitors in our screen. Previous studies described antihistamines, neuroleptic drugs, and other ligands of GPCRs as inhibitors of HCV entry (16,43,44). In the future, it would be interesting to test if the viral resistance mutations against any of these drugs eventually confer cross-resistance to piperazinylbenzenesulfonamides.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our laboratory identified multiple candidate compounds as late-stage HCV inhibitors via high-throughput screen [12]. In the current study, we validated and characterized MLS000833705, a late-stage HCV inhibitor, as a molecular probe for viral assembly and potential candidate for therapeutic development.…”
Section: Introductionmentioning
confidence: 84%